Climate change and risk management policies in viticulture - Filippo Sgroi; Vito Domenico Sciancalepore (Journal of Agriculture and Food Research, 2022)
In recent years, the adverse effects of climate change on agricultural productivity have been increasing dramatically. As a function of this situation, in many territorial contexts, productivity and profitability decrease due to uncontrollable events. In light of this situation, the entrepreneur should adopt strategies to decrease the risks of climate change and sustain agricultural productivity and farm profitability. The research used case studies of several wine-growing facilities of companies located in the Mediterranean area. The study estimated the losses of productivity and thus income due to climate change, which is occurring with increasing intensity. Subsequently, through the insurance model offered by the public operator with the European Agricultural Policy (CAP), it was analyzed that the adoption of climate change adaptation strategies, such as access to the insurance market, can reduce the risk of climate change and thus favor constancy of farm profitability. The empirical results revealed that the production of quality wines, the age of the entrepreneur, and the level of education are variables that favor access to the insurance market by wine-growing enterprises. On the other hand business income, especially of small enterprises, can be boosted by the adoption of these risk mitigation strategies. However, despite the positive benefits of adopting insurance policies, there is currently low adherence by enterprises. To improve farmers' ability to adapt to increasing climate change, insurance contracts should be promoted and competition between insurance companies should be fostered, which would guarantee a decrease in the cost of policies. This seems important for the overall sustainability of the wine sector and agriculture in general.